2022
DOI: 10.1007/s40195-021-01370-7
|View full text |Cite
|
Sign up to set email alerts
|

Reveal Hydrogen Behavior at Grain Boundaries in Fe–22Mn–0.6C TWIP Steel via In Situ Micropillar Compression Test

Abstract: In this study, the effect of hydrogen on dislocation and twinning behavior along various grain boundaries in a high-manganese twinning-induced plasticity steel was investigated using an in situ micropillar compression test. The compressive stress in both elastic and plastic regimes was increased with the presence of hydrogen. Further investigation by transmission electron backscatter diffraction and scanning transmission electron microscope demonstrated that hydrogen promoted both dislocation multiplication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The results revealed that deformation twins were also preferred nucleation sites of hydrogen-assisted cracks. Lu et al [15] investigated the effect of hydrogen on the deformation behavior of a HMnS using an in situ micropillar compression test and found that hydrogen promoted both dislocation multiplication and twin formation. In a previous study [16], we found that hydrogen would assist the nucleation of stacking fault (SF) and formation of deformation-induced martensite in a Fe-27.81Mn-0.3C (in wt%) twinning-induced plasticity (TWIP) steel.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that deformation twins were also preferred nucleation sites of hydrogen-assisted cracks. Lu et al [15] investigated the effect of hydrogen on the deformation behavior of a HMnS using an in situ micropillar compression test and found that hydrogen promoted both dislocation multiplication and twin formation. In a previous study [16], we found that hydrogen would assist the nucleation of stacking fault (SF) and formation of deformation-induced martensite in a Fe-27.81Mn-0.3C (in wt%) twinning-induced plasticity (TWIP) steel.…”
Section: Introductionmentioning
confidence: 99%